Current Molecular Therapeutic Agents and Drug Candidates for Mycobacterium abscessus - Quang, Nguyen Thanh; Jang, Jichan (Frontiers in Pharmacology, 2021)
Mycobacterium abscessus has been recognised as a dreadful respiratory pathogen among the non-tuberculous mycobacteria (NTM) because of misdiagnosis, prolonged therapy with poor treatment outcomes and a high cost. This pathogen also shows extremely high antimicrobial resistance against current antibiotics, including the anti-tuberculosis agents. Therefore, current chemotherapies require a long curative period and the clinical outcomes are not satisfactory. Thus, there is an urgent need for discovering and developing novel, more effective anti-M. abscessus drugs. In this review, we sum the effectiveness of the current anti-M. abscessus drugs and drug candidates. Furthermore, we describe the shortcomings and difficulties associated with M. abscessus drug discovery and development.